ACID-BASE EQUILIBRIUM IN THE SURFACE WATERS OF THE HUMID ZONE - Lozovik P.A. (My University, 2007)
The greatest variability is characteristic for the alkalinity of water and for concentration of hydrocarbonates and anions of organic acids. The acidity of the waters vary less significantly than these parameters. Because the Al concentrations are very low, it does not appreciably affect the acidity of waters, and this also pertains to Fe. The latter element occurs in waters as particulate matter and dissolved humic complex compounds [4]. Considering the maximum Fe concentration in these waters (4.6 mg/l or 0.08 mmol/l) with regard for the particulate mode of Fe in Karelian surface waters (50%) and its dissolved complex compounds (70% of all of its dissolved species), the Fe contribution to the acidity of the water at the complete first hydrolysis reaction of the cation ionic Fe compounds does not exceed 0.01 mmol/l.